DAMPAK PROGRAM KELUARGA HARAPAN PADA PENINGKATAN EKONOMI MASYARAKAT DI DESA SRAMBAH, PROPPO, PAMEKASAN - Hasir; Sakinah; Fahrurrozi (STIE Bakti Bangsa Pamekasan, 2023)
The Family Hope Program is a conditional cash assistance provided by the government to alleviate poverty and improve the welfare of its people. Based on this, there are two problems that are the main study in this research, namely; First, how is the implementation of the Family Hope Program (PKH) in Srambah Village, Proppo District, Pamekasan Regency. secondly, what is the economic level of the community with economic empowerment through PKH in Srambah Village, Proppo District, Pamekasan Regency.This research has the objectives, namely; First, to find out about the implementation of the Family Hope Program (PKH) in Srambah Village, Proppo District, Pamekasan Regency. Second, to find out what the economic level and income of the community is after the community economic empowerment through PKH, especially for PKH recipients in Srambah Village, Proppo District, Pamekasan Regency. This research uses a descriptive qualitative approach where the data sources used are primary and secondary data. Meanwhile, the data collection procedure for this research uses semi-structured interviews, non-participant observation and the informants in this research are PKH assistants, Srambah Village Head, Srambah Village officials and Srambah Village PKH participants.The results of this research are first, the implementation of PKH in Srambah Village, which includes right on target, cash assistance, honest and fair, graduated, while the procedures for receiving PKH are data verification and validation, group formation, disbursement and data updating. Secondly, the economic level of the Srambah Village community after empowerment through PKH has increased, especially for PKH participants who use this assistance to become entrepreneurs. This can be seen from several factors, namely in terms of income, wealth ownership, type of residence and education. However, the empowerment was not optimal because the Srambah Village PKH participants were still confused about developing their businesses, as stated by them, while receiving assistance, there had been no kind of training carried out to improve the skills and abilities of the Srambah Village PKH participants.